Pengembangan Fitur Rekapitulasi Kehadiran Karyawan pada Aplikasi e-HRD Perusahaan Menggunakan Metode Waterfall - Akbarakah Anzalna; Vina Ayumi (JSAI (Journal Scientific and Applied Informatics), 2025)
This study aimed to design and develop an attendance system for employees at PT. Nusrabil Grafika, including those working in the office (Work From Office/WFO) and those working from home (Work From Home/WFH). The main limitation of conventional attendance systems was their dependence on physical location, which restricted attendance recording to employees present at the office. This made it difficult to manage the attendance of employees working remotely and reduced operational efficiency, especially in companies with complex organizational structures and a large number of employees. The research followed the system development phases, including literature review, data collection, needs analysis, system design, implementation, and integration and testing. The hardware used in the system development was an Asus TUF Gaming laptop, while the software used included Sublime Text for coding and Visual Studio Code for debugging and team collaboration. The system was designed to manage and monitor employee attendance in real-time, providing various features such as employee data management, attendance recording, absence limit warnings, and attendance reports.